(untitled) (Unilorin Journal of Lifelong Education, 2025)
This study was designed to examine the role of Community psychologists in Community Development practices in Ifedore Local Government Area of Ondo State, Nigeria. Five (5) research questions were raised to guide the study. The descriptive survey research design was employed for the study and a total of two hundred and ten (210) respondents constituted the sample size for the study. The sample was selected through purposive sampling techniques. The questionnaire and a checklist designed by the researcher was the major instrument used for data collection. The questionnaire and checklist were validated by the experts fromthe Ministry of Community Development and Cooperative Services, Akure Ondo State, Nigeria, and Department of Adult and Non-formal Education, Faculty of Education, University of Benin, Benin City, Nigeria.Thereliability index was determined through the Pearson Product Moment Correlation Coefficient which produced a reliability index of 0.75. Data collected were analyzed using frequency counts and simple percentages for all the research questions examined. The study found out that those community psychologists were available in the Ifedore Local Government Area of Ondo State. It was also revealed that community psychologists work hand-in-hand with the community, give adequate information on the roles of the people in the community development activities, are involved in conflict resolution, and help ensure that community development programmes are carried out in accordance with the psychological needs of the community members. In view of the findings and conclusions from the study, it was recommended that more awareness needs to be created to inform people about the activities of community psychologists in community development practices, the communities should also create the enabling environment needed for community psychologists to strive and perform their responsibilities effectively and efficiently.